2018
DOI: 10.1038/s41594-018-0142-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-induced cell death relies on SLFN11-dependent cleavage of distinct type II tRNAs

Abstract: Transcriptome analysis revealed a strong positive correlation between human SLFN11 expression and the sensitivity of tumor cells to DNA damaging agents (DDAs). We show here that SLFN11 preferentially inhibits translation of ATR or ATM upon DDAs treatment based on distinct codon usage without disrupting early DNA damage response signaling. Type II tRNAs, which include all serine and leucine tRNAs, are cleaved in a SLFN11-dependent manner in response to DDAs. mRNAs encoded by genes with high TTA (Leu) codon usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 28 publications
7
127
1
Order By: Relevance
“…This aspartate is near a histidine in NONU-1 and forms the conserved DxH motif. More distant branches of the IF3-C fold include domains that bind, cleave, or process RNA, including the RNAseG/E nucleases (Fukui et al 2008), the synaptojanin/calcineurin domain phosphoesterases and nucleases , the Schlafen domain endoribonucleases (Makarova et al 2001;Li et al 2018;Yang et al 2018), and the RtcA RNA end cyclases ( Figure S3B, (Palm et al 2000)).…”
Section: Evolution Of Nonu-1 and Smr-domain Proteinsmentioning
confidence: 99%
“…This aspartate is near a histidine in NONU-1 and forms the conserved DxH motif. More distant branches of the IF3-C fold include domains that bind, cleave, or process RNA, including the RNAseG/E nucleases (Fukui et al 2008), the synaptojanin/calcineurin domain phosphoesterases and nucleases , the Schlafen domain endoribonucleases (Makarova et al 2001;Li et al 2018;Yang et al 2018), and the RtcA RNA end cyclases ( Figure S3B, (Palm et al 2000)).…”
Section: Evolution Of Nonu-1 and Smr-domain Proteinsmentioning
confidence: 99%
“…This selective effect of WNV on only a subset of tRNAs highlights their differential susceptibility to these virally exploited regulatory mechanisms. In support of this view, enzymes catalyzing tRNA posttranscriptional modifications, processing, and degradation, which importantly impact tRNA abundance, exhibit tRNA preferences (25,(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 89%
“…We speculate that Slfn11-mediated, WNV infection-triggered degradation of these four tRNAs requires levels of Slfn11 higher than those found in A172-SCR cells. In support of this interpretation, it has been reported that transient overexpression of Slfn11 preferentially degrades a subset of tRNAs (25), potentially impairing protein expression from cotransfected plasmids in an unspecific manner (3). Nevertheless, WNV replicated similarly in A172-SCR and -BC cells, indicating that changes in the abundances of these four tRNAs did not impact WNV replication.…”
mentioning
confidence: 92%
“…While mouse Slfns have been reported to function in immune response and lymphocyte development, functions of human SLFNs have not been well studied until recently [2][3][4]. SLFN11, a putative DNA/RNA helicase, has lately been analyzed from multiple aspects such as DNA damage response [5,6], RNA cleavage [7], and defense of viral infection [8][9][10]. As for the role in DNA damage response, accumulative studies have shown that SLFN11 augments sensitivity to a wide range of DNA-damaging agents such as platinum-derivatives, topoisomerase inhibitors, PARP inhibitors and replication inhibitors [4][5][6][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%